Alpine Trekkers and Tours: economic condition and its impacts on tourism industry of Pakistan. Issue 2 (9th July 2019) - Abbas, Syed Shaan; Akhtar, Muhammad
Abstract : Learning outcomes: The paper has the following learning outcomes: to understand the historical and geographical aspect of Pakistan vis-à-vis other countries of South East Asia and the world; to be able to understand the different marketing strategies of the tourism company; to gather the knowledge of many unknown facts which remain out of sight and hardly surface; to boost economy if its facts and figures are given due weight age and followed with true letter and spirit; and to give a big boost to an industry which remains mostly dormant for many decades. The ratio analysis of service sector is explained. How finances can be arranged in shortest time and generates profitability for the company is also discussed. Case overview/synopsis: The study provides an overview on the following topics: lack of interest by the Government in promotion; training of tour operators and guide; and managing the expected income from this industry. This study makes the masses aware that how much potential exist in the field of tourism in Pakistan. How the tour operators find huge potential in all segments of tourism and how the big force of trained manpower can be formed and creates employment. Service sector mostly run on equity finances because of lack of collateral, how efficiently they manage the finance for the business year. It gives details of extensive marketing strategy, the huge profit margin in foreign currency and cost volume profit systems of tourism companies. Complexity academic level: BBA, MBA and MS. Supplementary materials: Teaching Notes are available for educators only. Please contact your library to gain login details or email support@emeraldinsight.com to request teaching notes. Subject code: CSS 1: Accounting and Finance.